TINGKAT KONTAMINASI ESCHERICHIA COLI PADA AIR DAN MAKANAN DI BEBERAPA RUMAH MAKAN DI WILAYAH KERJA PUSKESMAS OEPOI KOTA KUPANG TAHUN 2009 - Pingak, Meksy S.; Adu, Apris A.; Tira, Deviarbi S. (Jurnal Pangan Gizi dan Kesehatan, 2010)
The research is aimed at knowing or finding out the degree of Escherichia coli contamination on water and food at some eating places in the working region of Puskesmas Oepoi, Kota Kupang in 2009. This research is a descriptive observation of nature in the form of a cross-sectional design. There are three samples of eating places that have been determined according to the so-called purposive sampling. 15 samples of food and water for food preparation of the same amount have been used in this research. The use of such sample materials is based upon the recommendation by the International Commission of Microbiological Spesification on Food. Method of laboratory examination has been employed to measure all variables. The result of the laboratory examination on the samples of food indicates that the degree of Escherichia coli contamination in the food served in the three eating places is high. The same analysis is true with the water preserved for food preparation, i.e. the degree of contamination of Escherichia coli is high.